Accessibility of Urban Transport for People with Disabilities and Limited Mobility : Lessons from East Asia and the Pacific - Babinard, Julie (World Bank, Washington, DC, 2014)
Accessibility of transport is not always a priority in transport planning and implementation. There can be barriers in the physical environment and delivery of services that render transport inaccessible. The principle of the UN Convention on the Rights of Persons with Disabilities (CPRD) brings new momentum to ensuring accessibility in the delivery of transport infrastructure and services. The CRPD recognizes that obstacles and barriers to indoor and outdoor public facilities and buildings and the physical environment should be removed to ensure equal access by people with disabilities and all members of society. This note summarizes the analysis done of the accessibility features of recent transport projects in the East Asia and Pacific (EAP) region. It seeks to highlight good practice in national laws, policies and project implementation to improve the welfare of transport users across projects. The overarching objective is to suggest how to improve the implementation of accessibility features in transport projects for people with disabilities and people with limited mobility. Mobility and access requirements of people with disabilities should be considered by planning and designing barrier- free transport systems. This implies an understanding and identification of the circumstances that create barriers for people with disabilities. Many countries have made progress in reducing barriers in the transport environment, particularly in high income countries. Countries have implemented regulation and design guidelines which explicitly consider accessibility for people with disabilities.